NILAI EKONOMI KONSERVASI SAUJANA BUDAYA KAWASAN BOROBUDUR Sebuah Eksperimen Pilihan - Soeroso, Amiluhur (Journal of Indonesian Economy and Business, 2007)
The values of Borobudur cultural landscape has conferred important meaningsin many aspects for those who live in its surrounding area. However, its culturallandscape (natural and cultural horizon) is constantly facing of degrading quality whichaffecting the future existence of Borobudurâs site.This research aims to explore and monetarily quantify the benefit of Borobudurcultural landscape to support the conservation efforts using choice experimentframework. Data were obtained from sample visitors and structured questionnaire arechosen for assessment of economic benefit using choice experiment, an âexpressedpreferencesâ method to assess the total economic benefit of conservation zone.The results indicate that the total economic benefit of Borobudur area is veryhigh. Consequently, the public loss, which is caused by poor management policy, will bevery high in financial term. Therefore, the survival of Borobudurâs site in the future willfully depends on its sustainable development policy.Keywords: Borobudur, saujana budaya, nilai ekonomi, sustainable development.